The Implementation of Law in Bureaucratic Reform: Challenges and Solutions for Efficient Governance - Teguh, Adean (Journal of Legal and Cultural Analytics, 2024)
Bureaucratic reform through legal implementation is essential for achieving efficient, transparent, and accountable governance. This article examines the challenges faced in implementing laws to drive bureaucratic reform and explores viable solutions to overcome them. Key challenges include systemic corruption, resistance to change within a bureaucratic culture, overlapping regulations, weak law enforcement, and limited public participation. These obstacles hinder efforts to establish good governance and often result in inefficiencies in resource management and public service delivery. The article proposes a systematic and comprehensive approach to address these challenges. Simplifying regulations through harmonization and evidence-based policymaking is emphasized to reduce legal overlaps. Strengthening the enforcement of laws, including the imposition of strict sanctions for violations, is identified as a critical measure. Moreover, enhancing the competence of civil servants through legal education and professional training is recommended to foster a culture of innovation and accountability within the bureaucracy. Public participation is also highlighted as a vital factor in ensuring transparency and oversight in policy implementation. Drawing on best practices from other countries, the study identifies strategies that could be adapted to Indonesia’s context. It concludes that achieving efficient governance requires the collaborative commitment of government, society, and the private sector. By addressing these challenges with legal frameworks and strong governance principles, a reformed bureaucracy can significantly improve public trust and deliver better outcomes for citizens.